Effect of bio-economic traits on market value of live goats: A case study of indigenous goat breeds - YOGI, R K; VERMA, N K; JAIN, D K; SINGH, RISHIKANTA (The Indian Journal of Animal Sciences, 2015)
Small ruminants in developing countries are mainly kept by local pastoralists under low-input production systems. The livelihood of the flock holders can be enhanced by the technical and institutional interventions. In this study, effect of bio-economic traits including age (Ag), live body weight (Bw), milk production (Mp), order of lactation (Or), prolificacy (Pf), favorable mark (Fm) and breed (Br) on market value of live goat was investigated. Study revealed that magnitude of difference in various traits of breeds ranged from 200 to 800%. It was observed that extent of variation in bio-economic traits of descript breeds was comparatively lower in case of both categories of dairy and meat goat. Non-descript breeds of the goat animals including dairy and meat goat fetched higher price over the descript breeds. Multiple regression analysis was applied to identify the potential economic traits of the breed. Mp and Bw had a direct and significant influence on the market value of the dairy goat. Similarly, Bw influenced the market value of meat goat positively while Ag was found to have adverse influence. Economic traits namely Mp, Fm and Bw of the live goat animals were observed as significant characteristics affecting the market value directly. These characteristics may be important for obtaining price premium. Institutional and technical interventions to enhance the milk productivity and gain in body weight of the live goat animals may be a strategic approach to benefit this sector.